Effect of Cr Content in Temperature-Dependent Mechanical Properties and Strain Hardening of a Twinning-Induced Plasticity Steel - Artigas-Abuin, A; Allende-Seco, R (Elsevier Ltd, 2024)
This study aims at assessing and analyzing the effect on the mechanical behavior at temperatures between 25 °C and 350 °C of the Cr additions (5 % and 10 %) to a TWIP steel (Fe–22Mn-0.6C). We conducted tensile tests and characterized the microstructure after deformation by light microscopy, X-ray diffraction (XRD) and FEG-SEM-EBSD. Different temperature-dependent strengthening mechanisms were determined. Mechanical twinning, Dynamic Strain Aging (DSA), and slip bands were the predominant mechanisms, with a combination of them depending on the stacking fault energy (SFE). The SFE decreases with the chromium content and increases with temperature, influencing the percentage of mechanical twinning generated during plastic deformation and consequently, affecting the strain hardening rate (SHR). There exists a direct relationship between strain hardening rate with temperature of deformation and mechanical twinning. DSA was observed and its effect on strain hardening was analyzed in detail. © 2023 Elsevier B.V.